Flexible and Transparent Microwave–Infrared Bistealth Structure. Issue 8 (17th May 2019) - Zhang, Changlei; Wu, Xiaoyu; Huang, Cheng; Peng, Jinqiang; Ji, Chen; Yang, Jianing; Huang, Yijia; Guo, Yinghui; Luo, Xiangang
Abstract: A flexible and transparent microwave–infrared bistealth structure is proposed to avoid composite detection in the microwave and infrared bands. By combining intrinsic material properties with proper design, the proposed flexible metamaterial can simultaneously achieve high absorption in the microwave band, low emission the in infrared band, and optical transparency. The structure exhibits wide‐angle (40°), broadband (7.7–18 GHz), and high‐efficiency (>90%) absorption. Furthermore, by using the structure to cover a metallic column, a 10 dB reduction in radar cross section at 7.5–18 GHz is achieved. The thermal emissivity of the structure is about 0.23 in the infrared atmosphere window, which is close to that of metal. It is optically transparent and flexible due to the use of indium tin oxide films and polyvinyl chloride substrates. These unique and interesting properties promise it will find potential applications in various stealth fields. Abstract : A flexible and transparent microwave–infrared bistealth structure is presented. It exhibits high‐efficiency (>90%) absorption at a wide band (7.7–18 GHz) and low emissivity (≈0.23) in the infrared atmosphere window. The structure is transparent and flexible due to the use of indium tin oxide films and polyvinyl chloride substrates. These unique and interesting properties promise it will find potential applications in stealth fields.